Apnea Periodik akibat Patent Ductus Arteriosus Besar dan Bronkopneumonia pada Bayi Usia 2 Bulan - Clara Arta Uli Rahel; Shinta Nareswari (CV. Jasa Sukses Abadi, 2026)
Patent Ductus Arteriosus (PDA) is a congenital heart defect resulting from the failure of ductus arteriosus closure after birth. A large PDA may produce a significant left-to-right shunt, leading to pulmonary overcirculation, heart failure, recurrent respiratory infections, growth failure, and apnea. This case report aims to describe the clinical presentation, diagnostic approach, and comprehensive management of an infant with periodic apnea associated with a large PDA complicated by bronchopneumonia. A 2-month-old female infant was admitted with cold extremities, cyanosis, and recurrent episodes of apnea lasting more than 20 seconds, occurring 4 hours before hospitalization. The patient also had a productive cough, respiratory distress, and poor weight gain since birth. Physical examination revealed tachypnea, subcostal and substernal retractions, cold extremities, a continuous cardiac murmur, and undernutrition with a body weight of 2.7 kg. Chest radiography demonstrated right bronchopneumonia, while echocardiography confirmed the presence of a large PDA. The patient was diagnosed with periodic apnea secondary to a large PDA, accompanied by bronchopneumonia, undernutrition, and incomplete basic immunization. Management consisted of oxygen therapy, intravenous antibiotics, bronchodilator nebulization, captopril and furosemide administration, and high-calorie nutritional support. After 10 days of hospitalization, significant clinical improvement was observed, including resolution of apnea and cyanotic episodes, reduced respiratory distress, hemodynamic stabilization, and weight gain to 2.9 kg. This case highlights the importance of considering congenital heart disease in infants presenting with recurrent respiratory symptoms, apnea, and failure to thrive to ensure timely diagnosis and comprehensive management.